Differential Phytotoxic Impact of Plant Mediated Silver Nanoparticles (AgNPs) and Silver Nitrate (AgNO3) on Brassica sp. - Vishwakarma, Kanchan; Shweta,; Upadhyay, Neha; Singh, Jaspreet; Liu, Shiliang; Singh, Vijay P.; Prasad, Sheo M.; Chauhan, Devendra K.; Tripathi, Durgesh K.; Sharma, Shivesh (Frontiers in Plant Science, 2017)
Continuous formation and utilization of nanoparticles (NPs) have resulted into significant discharge of nanosized particles into the environment. Nanoparticles find applications in numerous products and agriculture sector, and gaining importance in recent years. In the present study, silver nanoparticles (AgNPs) were biosynthesized from silver nitrate (AgNO3) by green synthesis approach using Aloe vera extract. Mustard (Brassica sp.) seedlings were grown hydroponically and toxicity of both AgNP and AgNO3 (as ionic Ag+) was assessed at various concentrations (1 and 3 mM) by analyzing shoot and root length, fresh weight, protein content, photosynthetic pigments and performance, cell viability, oxidative damage, DNA degradation and enzyme activities. The results revealed that both AgNPs and AgNO3 declined growth of Brassica seedlings due to enhanced accumulation of AgNPs and AgNO3 that subsequently caused severe inhibition in photosynthesis. Further, the results showed that both AgNPs and AgNO3 induced oxidative stress as indicated by histochemical staining of superoxide radical and hydrogen peroxide that was manifested in terms of DNA degradation and cell death. Activities of antioxidants i.e. ascorbate peroxidase (APX) and catalase (CAT) were inhibited by AgNPs and AgNO3. Interestingly, damaging impact of AgNPs was lesser than AgNO3 on Brassica seedlings which was due to lesser accumulation of AgNPs and better activities of APX and CAT, which resulted in lesser oxidative stress, DNA degradation and cell death. The results of the present study showed differential impact of AgNPs and AgNO3 on Brassica seedlings, their mode of action, and reasons for their differential impact. The results of the present study could be implied in toxicological research for designing strategies to reduce adverse impact of AgNPs and AgNO3 on crop plants.